Exceptional Gifted in West Virginia: Reflections of a Teacher of the Exceptional Gifted on the State Program - Coon, Patricia (Journal of the American Academy of Special Education Professionals, 2018)
Who are the students who qualify as Exceptional Gifted in West Virginia? In West Virginia, Policy 2419: Regulation for the Education of Exceptional Students, defines giftedness and delineates the criteria for eligibility. Identified Gifted students are served in grades 1-8; Exceptional Gifted students are served in grades 9-12. To understand what is exactly meant by this policy, one must first understand the definition. Giftedness refers to exceptional abilities and the potential for achievement that requires specially designed instruction and/or services beyond those provided in the general education classroom instruction (Policy 2419, 2017). In eighth grade in West Virginia, if a student who is gifted is underachieving, has a disability, is culturally and/or socioeconomically disadvantaged, and/or psychologically maladjusted, he may qualify for services in high school to keep him connected to school and to graduate. This paper explores the identification process for Gifted and Exceptional Gifted in West Virginia, as well as a teacher’s reflections on how to best serve these students through a program that is tailored to their specific needs, which can also serve as ideas for other programs of this nature.